Legal Certainty Of The Application Of The Systematic Lex Specialis Principle In Indonesian Criminal Tax Law - Saat, Eli; Iryani, Dewi; Rae, Gradios Nyoman Tio (Ilmu Hukum Prima (IHP), 2026)
This study examines legal certainty in applying the lex specialis systematicis principle within Indonesian criminal tax law. As a branch of special criminal law (bijzonder strafrecht), tax law faces enforcement issues due to overlap and potential conflict with general criminal provisions in the KUHP. The principle asserts that a rule is “special” if designated by the legislator or if it deviates from other specific norms, ensuring tax law is applied within clear legal boundaries. The research uses a juridical-normative method with statutory and conceptual approaches. It analyzes relevant legislation on taxation and general criminal law, alongside legal doctrines, expert opinions, and court decisions. Findings show that Indonesian criminal tax law possesses systematic specificity, meaning tax provisions should take precedence over general criminal rules in handling tax offenses. This applies to both substantive and procedural aspects, including offense classification, sanctions, and mechanisms such as limited reverse burden of proof. However, debate persists بشأن whether criminal tax law fully qualifies as special criminal law and whether the lex specialis systematicis principle applies absolutely. Legal certainty remains challenged by inconsistent interpretation and application. The study concludes that stronger legal harmonization and consistent jurisprudence are required to ensure clarity, fairness, and reliability in tax law enforcement.